Pervasive punishment : making sense of mass supervision - McNeill, Fergus (Emerald Publishing Limited, 2019)
This book challenges the centrality of the prison in our understanding of punishment, inviting us to see, hear, imagine, analyse and restrain 'mass supervision'. Though rooted in social theory and social research, its innovative approach complements more conventional academic writing with photography, song-writing and storytelling.